The Necessary Training Needs for UNRWA Schools Teachers in the Light of E- Learning from the Principals' Points of View - Marshood, Jamal Mohammad; Ibrahim, Asma' Osamah; Ghawadrah, Suar Maezuz; Salih, Raghad Hasan; Najaar, Bayan Adil (Journal of Educational and Psychological Sciences, 2022)
The purpose of the present study is to know the necessary training needs for UNRWA school teachers in the light of e- learning from the principals' points of view. The researcher used a descriptive approach, The tool of the study was a questionnaire which consisted of (42) items distributed among four fields (computer driving, internet leadership, e- learning culture, educational software and multimedia), the sample of the study consisted of (96 School Principal and Assistant School Principal) at the scholastic year 2020/2021, The statistical analyses were carried out by using SPSS, the researcher used (T- Test، One Way Anova) to answer the study questions. The study found out that the total degree of training needs necessary for UNRWA school teachers in light of e- learning from the principals’ points of view got a total average of ((3.33 out of 5), which meant it had a (moderate) degree, Meanwhile, at the fields level, the computer driving field got the highest average (3.70) with a (high) degree, then the Internet leadership field got an average of (3.46) with a (high) degree, then the e- learning culture field got an average of (3.30) with a (medium) degree, and finally the Educational software and multimedia field got an average of (2.81) a (medium) degree, there weren't significant differences attributed to gender and educational area variables on all fields, and there were significant differences attributed to qualifications variable in favor of more than bachelor’s degree.
Keywords: Ttraining Needs; E- learning